In vivo diagnosis of allergic diseases—allergen provocation tests. Issue 4 (12th February 2015) - Agache, I.; Bilò, M.; Braunstahl, G.‐J.; Delgado, L.; Demoly, P.; Eigenmann, P.; Gevaert, P.; Gomes, E.; Hellings, P.; Horak, F.; Muraro, A.; Werfel, T.; et al.
Abstract: The allergen challenge test has been the mainstay of diagnosis of allergic diseases for a long time since it offers a direct proof of the clinical relevance of a particular allergen for the allergic disease symptoms and severity. Standardisation and availability for daily practice (including safety issues) are still to be refined but most of the challenge tests have safely crossed the border from research tools to diagnostic tests available for daily practice for a well trained clinical staff.